Geographical Differences in the Management and Outcomes of Patients With Advanced Urothelial Carcinoma Treated With Pembrolizumab After Progression on Platinum-Based Chemotherapy: Results From ARON-2 Study - Mimma Rizzo; Andrey Soares; Shilpa Gupta; Fabio Calabrò; Hideki Takeshita; Maria Teresa Bourlon; Se Hoon Park; Patrizia Giannatempo; Zin War Myint; Thomas Büttner; Enrique Grande; Ondrej Fiala; et al. (JCO Global Oncology)
PURPOSEOur investigation assessed the impact of geographical disparities in the treatment of patients with advanced urothelial cancer (aUC) included in the international, real-world ARON-2 trial.PATIENTS AND METHODSThe study population comprised 1,137 patients with aUC treated with pembrolizumab for relapsed or progressive disease after platinum-based chemotherapy (PBC) at 63 institutions in 19 countries. Patients were divided into three geographical areas: Europe (area 1: 791 patients), the United States (area 2: 156 patients), and Asia (area 3: 190 patients). Clinicopathologic and treatment data were extracted from medical records. The primary end points were to identify differences in patient and treatment characteristics and to assess overall survival (OS) and progression-free survival (PFS) between the three areas.RESULTSThere were differences in patient characteristics: more patients age 70 years and older in area 1; more patients with BMI ≥25 kg/m2, squamous histotype, and T1 neoplasia at diagnosis in area 2; and more pure urothelial carcinoma in area 3. There were differences in treatment characteristics: Bacillus Calmette-Guérin instillations and primary tumor surgery were more common in area 1; neoadjuvant and adjuvant PBC, third-line therapies, and specifically enfortumab vedotin (EV) were less common in area 1. Median OS (mOS) from pembrolizumab initiation was 13.0 months in area 1, 29.1 months in area 2 and 13.2 months in area 3 (P < .001), and median PFS was 4.8 months, 5.2 months, and 3.8 months, respectively (P = .002). In patients receiving EV after progression to PBC and pembrolizumab, mOS was 44.1 months in area 1, 31.7 months in area 2, and 23.8 months in area 3 (P = .267).CONCLUSIONReal-world data suggest that facilitating and extending access to targeted therapies for patients with aUC in different geographical areas worldwide may lead to a consistent and widespread survival increase.